Kelimpahan Serangga akibat Beberapa Teknik Pengendalian pada Tanaman Kacang Panjang (Vigna sinensis L.) - Rahmadianti, Shifani Shintya; Afifah, Lutfi; Adhi, Satriyo Restu; Irfan, Budi (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2024)
The decline in the production of long beans in Indonesia is one of the causes of a pest attack. The majority of farmers in Indonesia, still use synthetic pesticides as a pest control effort. The aim of this research is to obtain a pest control technique that gives the lowest result against insect abundance in long bean crops. (Vigna sinensis L). The study used a single factor random group design (RAK) method with 6 repetitions and 4 treatments including: No Treatment/Control (K), Biointensive Control (PB), Combined Control (PK) and Synthetic Control. (PS). The sampling of insects is done using 3 traps: yellow traps, pitfall traps and insect net traps. Sampling is done 10 times, starting from 1 – 10 mst. The data analyzed using a scale fingerprint, on a different real result will be performed a further trial of the Minimum Real Difference with a degree of 5%. PS control shows the results of the analysis with the lowest average abundance on insect net trap (SNT) of (130.17) and pitfall trap (PFT) of (147.50) different real from other treatments, but no real difference on yellow board trap (YST) of size (104,50).